2015
DOI: 10.3892/mmr.2015.4494
|View full text |Cite
|
Sign up to set email alerts
|

Role of histone deacetylase 3 in ankylosing spondylitis via negative feedback loop with microRNA-130a and enhancement of tumor necrosis factor-1α expression in peripheral blood mononuclear cells

Abstract: The present study was performed to investigate the molecular mechanism of ankylosing spondylitis (AS). The interaction between micro (mi)RNA-130a and its target tumor necrosis factor (TNF)-1α and histone deactylase (HDAC)3 was assessed in peripheral blood mononuclear cells (PBMCs) from AS patients. Increased HDAC3 and decreased miRNA-130a levels were observed in PBMCs from AS patients. HDAC3 knockdown or HDAC3 inhibition promoted the expression of miRNA-130a, and HDAC3 was recruited to the promoter region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Jiang and Wang () reported several critical observations regarding the participation of histone deacetylase (HDAC) 3 in the molecular mechanisms of AS. First, augmented mRNA and protein levels of HDAC3 and reduced levels of miRNA‐130a were found in PBMCs from AS patients.…”
Section: Biogenesis Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang and Wang () reported several critical observations regarding the participation of histone deacetylase (HDAC) 3 in the molecular mechanisms of AS. First, augmented mRNA and protein levels of HDAC3 and reduced levels of miRNA‐130a were found in PBMCs from AS patients.…”
Section: Biogenesis Of Mirnasmentioning
confidence: 99%
“…In contrast, downregulation of let-7i suppressed IFN-γ production by anti-CD3 + anti-CD28+ LPS-stimulated AS T cells. Nonetheless, the downstream molecular mechanism of upregulated let-7i expression stimulating a T helper type 1 (Th1) (IFN-γ) immune response needs more detailed researches Jiang and Wang (2016). reported several critical observations regarding the participation of histone deacetylase (HDAC) 3 in the molecular mechanisms of AS.…”
mentioning
confidence: 99%
“…More importantly, it can prevent disturbance of normal immune function (8). Jiang and Wang (10) indicated that histone deacetylase 3 was involved in ankylosing spondylitis via miR-130a and enhancement of tumor necrosis factor-1α (TNF-1α) expression. Li et al (11) showed that miR-130a played an important role in regulating the expression of TNF-α in osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a few surveys have inspected AS etiopathogenesis under the light of epigenetic aberrations. These studies focused on DNA methylation [110,111], histone modifications [112], and microRNAs [113][114][115][116]. Nonetheless, no study has evaluated the role of epigenetic dysregulation in susceptibility to AS applying twin pairs.…”
Section: Ankylosing Spondylitismentioning
confidence: 99%